Enhancing Malaysian public sector transparency and accountability: lessons and issues - Abu Bakar, Nur Barizah; Saleh, Zakiah; Mohamad, Muslim Har Sani (EuroJournals, Inc., 2011)
This paper discusses the possibilities and challenges for a developing country, particularly Malaysia, to emulate the more inclusive accountability practices of advanced countries. The paper contended that the objectives of performance measurement initiatives will not be achieved in promoting greater transparency and accountability unless their development is extended further through disclosures. This disclosure may consequently assist the relevant entities to aptly rate and rank those government agencies within its sectors. The paper concludes that there is a seemingly encouraging trend in Malaysian public sector toward greater transparency, and this can be further enhanced provided that Malaysia first addresses implementation issues and liberates itself from obsolete judgments and policies.